2019
DOI: 10.1364/oe.27.00a224
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive photoacoustic multicomponent gas sensor for SF6 decomposition online monitoring

Abstract: A ppb-level photoacoustic multicomponent gas sensor system for sulfur hexafluoride (SF 6) decomposition detection was developed by the use of two near-infrared (NIR) diode lasers and an ultraviolet (UV) solid-state laser. A telecommunication fiber amplifier module was used to boost up the excitation optical power from the two NIR lasers. A dual-channel high-Q photoacoustic cell (PAC) was designed for the simultaneous detection of CO, H 2 S, and SO 2 in SF 6 buffer gas by means of a time division multiplexing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…According to current researches (Yin et al, 2019;Zhang et al, 2018a;Zhang et al, 2018b), in the wavelength range between 198 and 310 nm, SO 2 exhibited two strong absorption band, which were between 190 and 220 nm ( 1 B 2 / 1 A 1 ) and 250 nm to 310 nm ( 1 A 2 , 1 B 1 / 1 A 1 ). H 2 S occurs with an absorption band between 160 and 250 nm.…”
Section: Methodsmentioning
confidence: 93%
“…According to current researches (Yin et al, 2019;Zhang et al, 2018a;Zhang et al, 2018b), in the wavelength range between 198 and 310 nm, SO 2 exhibited two strong absorption band, which were between 190 and 220 nm ( 1 B 2 / 1 A 1 ) and 250 nm to 310 nm ( 1 A 2 , 1 B 1 / 1 A 1 ). H 2 S occurs with an absorption band between 160 and 250 nm.…”
Section: Methodsmentioning
confidence: 93%
“…Besides, the accumulate of these chemically active decomposition gases with the action of H 2 O will corrode electrodes and reduce the insulating performance of the electrical equipment, and may ultimately pose an assault to industrial safety. It has been experimentally verified that the SF 6 decomposition gas concentrations and formation rates are associated with the different partial discharge insulating faults [14] , [15] , [16] . Moreover, Tang et al [17] in 2012 found that the production of CF 4 was inhibited, but the generation of SOF 2 and SO 2 F 2 was promoted with the increasing of O 2 concentration.…”
Section: Introductionmentioning
confidence: 94%
“…Conventionally, the gas sensing system needs a bulky gas chamber to ensure a strong light-gas interaction for low detection limit [36][37][38] . As is well known, micro-resonators are usually used to enhance the light-matter interaction 30 , which is able to reduce the sensor dimensions for distributed or low-load platform while keeping a high performance.…”
Section: Mechanismmentioning
confidence: 99%